1998
DOI: 10.3141/1626-16
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice Evaluation: Wilmington Bypass, Wilmington, North Carolina

Abstract: Among the common mandates of agency guidelines implementing Executive Order 12898, Federal Actions to Address Environmental Justice in Minority Populations and Low-Income Populations, is the determination of whether the subject action or project will cause disproportionately high and adverse human health or environmental effects on minority or low-income populations. This determination is often troublesome because it requires the analyst to know or define disproportionate impacts. A method is provided for defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Researchers have also shown that environmental justice populations have higher exposure to air and noise from roadways ( 19 , 20 ). Efforts to improve the environmental justice of the transportation system have led to evaluations of proposed road construction projects ( 21 , 22 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have also shown that environmental justice populations have higher exposure to air and noise from roadways ( 19 , 20 ). Efforts to improve the environmental justice of the transportation system have led to evaluations of proposed road construction projects ( 21 , 22 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, analysis of EJ by transit agencies concerns three main areas of operations: long-range capital investment decision making, short-range service planning, and tactical day-to-day service delivery. Prior EJ research has described the data sources, processes, and challenges (7), particularly from the standpoints of highways (8,9), capital projects (10)(11)(12), and long-range planning (13,14) in areas as varied as Florida, the Carolinas, Chicagoland (northeastern Illinois), Southern California, and the San Francisco Bay area in California; but specific discussions from the viewpoints of operating authorities are rare in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beginning in the 1990s, several projects were initiated to upgrade transportation planning and investment tools to address the equity impacts of transportation investments (18)(19)(20)(21) in response to regulations requiring that agencies address the environmental justice impacts of federally funded projects (22). Several analysis tools seek to address not only the functional, economic, and environmental impacts of transportation investments but the social impacts as well, for example, the impacts of proposed improvements on the mobility of marginal populations.…”
Section: Evolving Measures Of Value In Transportation Infrastructure Investmentmentioning
confidence: 99%